PENGETAHUAN, SIKAP DAN PENGALAMAN CARETAKER TENTANG PENDIDIKAN KESEHATAN REPRODUKSI TUNAGRHITA DI SLB DHARMA WANITA KABUPATEN GRESIK - Qurrota Ayun; Zahroh Shaluhiyah; Ani Margawati (Dian Nuswantoro Semarang, 2019)
ABSTRACTBackground: Mental Retardation are those who have general intelligence below average, have limitations in terms of taking care of themselves and particularly vulnerable to sexual abuse because lack of reproductive health education. This study wants to describe the knowledge, attitudes and experience of the caretaker about mental retardation reproductive health education at SLB Dharma Wanita Gresik Regency. Method: This is a qualitative research. The data collection method uses Focus Group Discussion. Data were validated by triangulation of informan sources, crosscheck with teachers. Data analysis was performed by content analysis method. Results: Caretaker knowledge about mental retardation reproductive health education is a skill of self-development which includes the topic of toilet training, menstruation, and how to avoid danger. Caretaker agrees to provide mentally retarded reproductive health education from an early age adjusted to the child's ability to be independent. Obstacles experienced by caretakers related to child care, especially self-development, such as bathing, toilet training and difficulty in controlling children's emotions. Caretaker's experience in providing mentally retarded reproductive health education is to apply mentally retarded self-development materials (toilet training), and instilling shame in children by wearing towels from the bathroom. Conclusion: Mental retardation reproductive health education media needed as a guide caretaker.Keywords: Mental retardation, reproductive health education, caretaker